Sistem Informasi Geografis Letak Industri Kecil dan Menengah berbasis android di Provinsi Gorontalo - Senung, Bahtiar; Syaifuddin, Syaifuddin (Jurnal Teknologi Informasi Indonesia (JTII), 2020)
Small and Medium Industry is the program and policy of the Local Government of Gorontalo Province to achieve development goals in the field of economy, especially related to the development efforts of small and medium industry sectors (IKM). The Cooperative, Industrial and Trade Office of Gorontalo Province desperately needs accurate data information for the search and determination of small and medium industry locations and also in terms of regional development planning and spatial arrangement, but in reality, to obtain data and information on the spread of Small and Medium Industry spread almost throughout Gorontalo province is very difficult, this is due to the absence of an information system that handles this. The Government's current geographic information system cannot access the search and location of the Small and Medium Industry. The expansion of the area that occurs in Gorontalo Province from 6 districts, the addition of fickle regions and addresses can confuse and make it difficult for local people or tourists outside Gorontalo province to get information about the small and medium industry in Gorontalo Province. The lack of information to the public about the location of Small and Medium Industry locations in Gorontalo province can make it difficult to conduct cooperation that can drive the regional economy. Information search and access user information and communication technology through high mobility media such as smartphones. Today's thriving smartphones are smartphones with android operating systems. Android smartphone besides having high mobility, also has very useful features such as google maps and GPS. Google maps and GPS features can collaborate in an android app program creation. Application program creation is designed using android and PHP programming languages collaborated with MySQL databases as data container media. The research aims to make it easier for people to get information about small and medium-sized industries and information about small and medium-sized industries. The availability of information can be a bridge for the community to cooperate and drive the regional economy.